P2_5 Bun in the Oven - Stinton, James; Murgatroyd, Conan; Kinsman, Charlie; Mott, Dan (Physics Special Topics, 2021)
This paper estimates the total monetary cost of making a cake sufficient to provide the extra calories a woman requires over the course of a standard pregnancy. The total extra calorie intake was determined to be 18600 kcal, the mass of the cake was calculated to be 6.4 kg and the total monetary cost was found to be £16.43.